Ecosystem services produced by groundwater dependent ecosystems: a framework and case study in California - Howard, Jeanette K.; Dooley, Katherine; Brauman, Kate A.; Klausmeyer, Kirk R.; Rohde, Melissa M. (Frontiers in Water, 2023)
Groundwater is an important freshwater supply for agricultural, domestic, and environmental uses, and critical buffer against a warming climate particularly in semi-arid and arid regions of the world. Groundwater-dependent ecosystems (GDEs), which rely on groundwater for some or all of their water requirements, include terrestrial vegetation, rivers, springs, wetlands, and riparian zones. These GDEs provide benefits to people ranging from habitat for pollinators to carbon sequestration. Accounting for these benefits, called ecosystem services, can inform management by expanding the potential group of groundwater users. We identify the ecosystem functions of a range of GDEs and explain how they are linked to protection of wide range of ecosystem services. These functions inform criteria for determining if a specific GDE is producing a certain service. In addition, we identify criteria for determining who is benefiting from provision of the service and if there are spatial relationships that need to be considered. Applying this framework in California, we find that provision of pollination services is widespread across the state. Over 30% of California’s pollinator dependent crops may benefit from GDEs, and carbon storage of GDEs is equivalent to 790 million tons, twice as much as California emits annually.